Exploitation of and damage to reputation : trade-mark protection in respect of dissimilar goods and services in South African and German law of unlawful competition - Schmidt, Robert M.(Robert Michael) (Stellenbosch : Stellenbosch University, 2012)
Thesis (LL. M.) -- University of Stellenbosch, 1998.